HUBUNGAN TINGKAT AKTIVITAS FISIK DENGAN DERAJAT NYERI PUNGGUNG BAWAH PADA WARGA USIA PRODUKTIF DI RW 11 KELURAHAN HARJAMUKTI KOTA DEPOK TAHUN 2022 - Bowo Laksono, Abdurrahman Berbudi; Layyina, Fatimah Zahra Nur; Sariana, Erna (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Background: Low back pain is a common problem in various age groups. One of the factors that influence low back pain is the amount and type of activity performed. This study aims to analyze the relationship between the level of physical activity and the degree of low back pain. Research Methods: This study used cross-sectional research design and was conducted on residents of productive age in RW 11, Harjamukti, Depok from April to May 2022. A sample of 106 people was taken using purposive sampling technique. Data analysis includes univariate and non-parametric bivariate analysis using the Spearman Rank test. Results: Respondents with a level of physical activity based on IPAQ with a low category of 9.4%, a medium category 68.9%, and a high category 21.7%. The average degree of pain using the NPRS was 3.44. The results of statistical tests obtained significance value 0.000 (<0.05) with a correlation coefficient of -0.41. Conclusion: There is a significant relationship between the level of physical activity and the degree of low back pain in residents of productive age. The correlation is negative with sufficient strength.